Validasi Metode Spektrofotometri UV-Vis untuk Analisis Octyl Methoxycinnamate (OMC) pada Sampel Powder Tabir Surya.: Validation of UV-Vis Spectrophotometric Method for the Analysis of Octyl Methoxycinnamate (OMC) in Sunscreen Powder Samples. - Risma Eka Cahyani; Aditya (Universitas Gunadarma, 2026)
Indonesia has a high intensity of sun exposure (Ultraviolet). To protect the skin from these UV rays, it is recommended to use cosmetics that contain special compounds as sunscreens, namely octyl methoxycinnamate (OMC). BPOM recommends the maximum concentration of OMC in sunscreen cosmetics is 10%. This study aims to validate the method of analysing OMC levels using UV-Vis spectrophotometer in loose powder sunscreen preparations that have been circulating. The validation method includes specificity, linearity, accuracy, precision, BD and BK. The optimal solvent was isopropanol, showing a linear regression equation y = 0.1003x + 0.0111; R² = 0.9998. Validation of the analytical method: λmax specificity of OMC standard 308.5 nm; linearity y = 0.1006x + 0.0102; R² = 0.9999. The % recovery values with concentrations of 80%, 100% and 120%, namely 122.18%; 113.88%; 106.66%. The % RSD values were 0.68%; 0.15%; 0.18%. BD value = 0.68 µg/mL; and BK = 2.06 µg/mL. The loose powder sunscreen sample A was 1.42% (b/v). Sample B was 0.22% (b/v) and sample C was 1.69% (b/v). OMC in sunscreen cosmetics fulfils the requirements recommended by BPOM.